PENGARUH PEMASANGAN TRASHBOOM TERHADAP KECEPATAN ALIRAN DI SUBDAS BENDUNG - Miranda, Ade Tricia (Universitas Muhammadiyah Palembang, 2023)
The large amount of rubbish in the river flow in the Bendung sub-basin has prompted the government to create an innovation to deal with this problem. This innovation is the installation of trash booms at critical points. However, the installation of the trash boom is thought to slow down the flow downstream, causing a delay in the time for the river water level to recede. After conducting a comparative analysis of river flow velocity using a current meter, it was found that there was a 34% decrease in flow velocity in the downstream part of the river, where the first flow velocity was 0.29993 m/s, decreasing by 0.10099 m/s to become 0.19894 m/s downstream after the trash boom installation point.